SHU00238 Promotes Colorectal Cancer Cell Apoptosis Through miR-4701-3p and miR-4793-3p - Wang, Haoyu; Ma, Yurui; Lin, Yifan; Chen, Rui; Xu, Bin; Deng, Jiali (Frontiers in Genetics, 2020)
Colorectal cancer is one of the most leading causes of death. Searching for new therapeutic targets for colorectal cancer is urgently needed. SHU00238, an isoxazole derivatives, was reported to suppress colorectal tumor growth through microRNAs. But the underlying mechanisms still remain unknown. Here, we explored the mechanism of SHU00238 on colorectal cancer by RT-PCR, CCK-8, flow cytometry, mirTarBase and GO enrichment analysis. We screened partial microRNAs regulated by SHU00238 in colorectal cancer cells. Furthermore, we identified that miR-4701-3p and miR-4793-3p can reverse the acceleration of SHU00238 on colorectal cancer cell apoptosis in HCT116 Cells. Finally, we found that SMARCA5, MBD3, VPS53, EHD4 are estimated to mediate the regulation of miR-4701-3p and miR-4793-3p on colorectal cancer cell apoptosis, which targets ATP-dependent chromatin remodeling pathway and endocytic recycling pathway. Taken together, our study reveals that SHU00238 promotes colorectal cancer cell apoptosis through miR-4701-3p and miR-4793-3p, which provide a potential drug target and therapeutic strategy for colorectal cancer.